Guerra à peste branca: Clemente Ferreira e a Liga Paulista contra a tuberculose 1899 -1947 - Rosemberg, Ana Margarida Furtado Arruda (2008)
The objective of this research is to show the war against Tuberculosis in São Paulo city from 1899 to 1947; the life and work of Clemente Ferreira, pioneer in the fight against Tuberculosis in Brazil, and, also the importance of this disease in popular language and in the minds of those working in this field at this time. Its describes the setting up and work of the Liga Paulista against Tuberculosis, a charitable organization founded in 1899 by Clemente Ferreira and collaborators, pointing out its main weapons: dispensary, prevention institution, sanatorium and hospital. Also included is the functioning of the model Clemente Ferreira Dispensary, the first of its kind in the struggle against Tuberculosis in São Paulo city in the first 30 years of the 20th century. Furthermore the role of the journal Defesa contra a Tísica the official organ of Liga Paulista in making the population and law makers aware of the importance of relating the seriousness of Tuberculosis and the necessity of the government to take responsibility and support the fight. This work also analyzes those involved in this area in popular language and in what they thought. It shows the importance of charitable associations at the beginning of the 20th century to make the control of Tuberculosis in Brazil and, specifically, in São Paulo city, a matter of interest and responsibility of the state